Novas t?cnicas de processamento digital para ajuda a portadores de defici?ncia auditiva com perdas em altas frequ?ncias - Marotta, Alan Mendes (2004)
A sizable percentage of hard hearing loss listeners presents audiograms where losses are large for high frequencies and small for low frequencies. For these cases, lowering the spectrum of frequencies to a range where there is some residual hearing may be a good solution for implementing a digital hearing aid. In this work two different frequency lowering algorithms are presented: compression and translation. Results of subjective tests of consonant discrimination showed that a better performance was observed when using the proposed processing algorithms.